Optimisation of phagocytosis assay in rainbow trout (Oncorhynchus mykiss) - H Minarova; P Ondrackova; M Palikova; J Mares; J Blahova; K Jarova; M Faldyna (Veterinární Medicína, 2021)
A phagocytosis assay is one of the most commonly used functional immunological methods. There are many possible ways of assessing leucocytes and their ability to ingest different particles. The aim of this study was to optimise the phagocytosis assay in rainbow trout (Oncorhynchus mykiss) using labelled zymosan particles (Alexa Fluor 488 and Texas Red conjugate). Whole blood was incubated with the particles under different conditions and leucocytes were subsequently isolated by haemolysis in a hypotonic environment. The effect of the different incubation time, temperature, blood volume and dilution on the phagocytic activity was evaluated by flow cytometry. Our experiments showed that the incubation for at least 2 h at 15 °C provided optimal results, while the blood volume and dilution had no significant effect. The optimised assay will be used for the examination of fish health and in further experimental studies.